How marketizing and technologizing education undermines spirituality - Ruth, Damian (Journal for the Study of Spirituality, 2023)
This paper takes education to be concerned with human flourishing, and education that is distinct from instrumental training and which attends to the spirit of students. Such education is holistic and integral and develops the capacity for sustained attention and concentration. Marketization does not, and its impact on education has been long decried. The use of technology in education has always been met with ambivalence. What comprises technology is not obvious, and aspects of it, especially developments in media, undermine sustained attention and concentration. Both marketizing and technologizing an impact on spirituality in education but how they do so in concert with one another and under the aegis of corporations warrants particular scrutiny, which to date has been insufficient, for their combined impact is greater than the sum of the parts. In this paper, markets are distinguished from marketization, and religion from spirituality and mindfulness from what has been labelled McMindfulness and positive psychology. The latter are critiqued for how they have been co-opted by marketization, technology and corporate interests. The conclusion of the paper is that the contemporary pain of educators and students and dysfunctional institutions arises from the loss of spirituality and purpose and that reversing this is essential for humanity’s well-being.